Diagnosis of Oral Hairy Leukoplakia: The Importance of EBV In Situ Hybridization - Luana L. Martins; José Henrique F. Rosseto; Natália Silva Andrade; Juliana Bertoldi Franco; Paulo Henrique Braz-Silva; Karem L. Ortega (International Journal of Dentistry)
Oral hairy leukoplakia (OHL) is caused by the Epstein-Barr virus (EBV), which has been related to HIV infection. In situ hybridization (ISH) is the gold-standard diagnosis of OHL, but some authors believe in the possibility of performing the diagnosis based on clinical basis. The aim of this study is diagnose incipient lesions of OHL by EBV ISH of HIV-infected patients and the possible correlations with clinical characteristics of the patients. Ninety-four patients were examined and those presenting with clinical lesions compatible to OHL were submitted to biopsy prior to EBV ISH. Twenty-eight patients had lesions clinically compatible to the diagnosis of OHL, but only 20 lesions were confirmed by EBV ISH. The patients with OHL had a mean age of 41.9 years and were HIV-infected for 11.2 years, on average, including CD4 count of 504.7 cells/mm3 and log10 viral load = 1.1. Among the quantitative variables, there was a statistically significant correlation with age only (P=0.030). In conclusion, the presence of OHL in patients with HIV/AIDS results in changes in the epidemiological characteristics of the disease, and this fact allied with subtle clinical-morphological features makes clinical diagnosis very difficult. Therefore, EBV ISH is important for a definitive diagnosis of OHL.